Fatal gastrointestinal manifestations of SLE: case reports - W. Lee Wan Hui, Lee; S. Benjamin, Sachdev; Sharifah Aishah, Wan Mohamad Akbar; C. Yaw Kiet, Cheong; D. Balakrishnan, Balakrishnan; Ahmad Tirmizi, Jobli; T. Cheng Lay, Teh (John Wiley & Sons, 2021)
Background: SLE- related gastrointestinal involvement such as gastrointestinal vasculitis and thrombosis are clinically important, as it could progress to life- threatening outcome if not treated promptly. We describe 2 patients who were admitted to our hospital with fatal gastrointestinal manifestations of SLE. Method: Case Report. Results: Case 1: The patient was a 24- year- old Asian woman who was diagnosed with SLE in 2014 and class IV lupus nephritis in 2018. She presented with hypovolemic shock secondary to massive hematochezia. CT abdomen and angiography revealed multiple bleeding sites in jejunum and mesenteric vasculitis changes of the bowels. Gastroduodenoscopy and CT angioembolization of the mesenteric arteries were performed to stop the bleeding, and IV Methylprednisolone, IV Cyclophosphamide, IV Rituximab were administered. Eventually she succumbed to Transfusion- Related Acute Lung Injury (TRALI) from multiple blood transfusions. Case 2: The patient was a 61- year- old male smoker who was diagnosed with SLE with lupus nephritis in April 2020. He however refused renal biopsy or cyclophosphamide. He presented a few months later with fever and colicky abdominal pain for 2 days. A diagnosis of Superior Mesenteric Artery (SMA) Thrombosis with Bowel Ischemia was made, which was likely due to Catastrophic Anti- Phospholipid Syndrome (CAPS) with SLE, based on CT abdomen findings of SMA thrombosis, bilateral common femoral vein thrombosis and multiple splenic infarcts. Heparin infusion was initiated, and he was administered IV Methylprednisolone and Intravenous Immunoglobulin (IVIg). He developed Disseminated Intravascular Coagulation (DIVC) subsequently and succumbed to his illness at day 2 of admission. Conclusion: In summary, early diagnosis with prompt and adequate treatment of gastrointestinal manifestation of SLE is essential to avoid serious complications like haemorrhage or perforation with a high mortality rate.